REFORMASI HUKUM DIBIDANG KEKAYAAN INTELEKTUAL TERKAIT PENGATURAN PERCEPATAN LAYANAN PATEN SEDERHANA - Andrewnov Marguratua; Elfrida Ratnawati Gultom (Ensiklopedia of Journal, 2023)
The presence of Law Number 11 of 2020 concerning job creation has caused pros and cons among legal experts. This is caused by the presence of this law, both from a formal perspective and in its composition, which is considered to have several problems. From a substantial perspective, it still causes problems in realizing the goals of the law. One of the most interesting substantial changes in terms of substantial changes to the provisions of Law Number 13 of 2016 concerning patents after the enactment of the Job Creation Law and its implications for accelerating simple patent registration services for determining the value of novelty To examine this matter, a study will be carried out on the formulation of the problem, namely, how is the law reform carried out related to the acceleration of simple patent registration? The formulation of this problem will use a normative research method. As for the conclusion, it is (1). There are several changes regarding simple patents in the work copyright law: (2) The changes that have taken place include simplifying the process for granting simple patents (3). Whereas the changes made to the work copyright law were formed in the context of accelerating public services, Whereas the changes that have been made must also be followed by the renewal of lower operational regulations such as government regulations or ministerial regulations Keywords: Simple Patent; Legal Reform ; Job Creation Law